PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V DI UPTD SDN LANDAK 1 TANAH MERAH (PIONIR: JURNAL PENDIDIKAN, 2023)
This study aims to determine the effect of the jigsaw type cooperative learning model on mathematics learning outcomes for class V at UPTD SDN Landak 1 Tanah Merah. This research uses a quantitative approach, the type of research is Pre-Experimental Designs One Group Pretest-Postest. The population in this study were all 15 students of class V UPTD SDN Landak 1 Tanah Merah. The t-test shows the correlation coefficient value of 0.796 with a sig value of 0.000